Analyzing Educational Achievement Differences Between Second-Generation Immigrants: Comparing Germany and German-speaking Switzerland - Johannes S. Kunz (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this study, I provide evidence that the educational achievement of second-generation immigrants in German-speaking Switzerland is greater than in Germany. The impact of the first-generation immigrants' destination decision on their offspring's educational achievement seems to be much more important than has been recognized by the existing literature. I identify the test score gap between these students that cannot be explained by differences in individual and family characteristics. Moreover, I show how this gap evolves over the test score distribution and how the least favorably-endowed students fare. My results suggest that the educational system of Switzerland, relative to the German system, enhances the performance of immigrants' children substantially. This disparity is largest when conditioning on the language spoken at home, and prevails even when comparing only students whose parents migrated from the same country of origin.
Keywords: I21; I24; J15; 330; immigrant comparison; educational achievement decomposition; Germany and Switzerland